Clinical manifestation of drug allergy in children - Ariyanto Harsono; Anang Endaryanto (Paediatrica Indonesiana, 1999)
In the period of January-December 18 cases of Drug Allergy were recognized, 4 cases from the allergy clinic, 8 cases were referred from outpatient clinic, 6 cases were referred from inpatient ward. The clinical manifestation varied from urticaria 5 cases (30%), Steven Johnson Syndrome 2 cases ( 12%), maculopapular rash 2 cases (12%), Drug fever 2 cases (12%), Fixed drug eruption 1 case (6%), exanthem 1 case (6%), Quinke's edema 5 cases (30%) consisted of 2 cases Quinke's edema only, 2 cases with urticaria, 1 case with drug fever. The underlying disease of these cases were upper respiratory tract infection 5 cases, chronic cough 2 cases, Asthma 5 cases, diarrhea 1 case cerebral abscess 1 case, Dengue Haemorrhagic Fever 1 case and Epilepsi 1 case. The mainstay of treatment was discontinuation of the offending drug. Drug substitution were given to patients nescessitated continuation of drugs, antihistamines were given to patients with urticaria and Quinke's edema. Two cases with Steven Johnson syndrome received supportive treatment and hydrocortisone intravenously.